1998
DOI: 10.1112/s002460939800455x
|View full text |Cite
|
Sign up to set email alerts
|

On Fuchsian Groups with the Same Set of Axes

Abstract: Let Γ be a Fuchsian group. We denote by ax(Γ) the set of axes of hyperbolic elements of Γ. Define Fuchsian groups Γ1 and Γ2 to be isoaxial if ax(Γ1) = ax(Γ2). The main result in this note is to show (see Section 2 for definitions) the following. THEOREM 1.1. Let Γ1 and Γ2 be isoaxial arithmetic Fuchsian groups. Then Γ1 and Γ2 are commensurable. This result was motivated by the results in [6], where it is shown that if Γ1 and Γ2 are finitely generated non‐elementary Fuchsian groups having the same non‐empty set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In the case of Fuchsian groups of the first kind Long and Reid [4] proved the conjecture for arithemetic groups. Also notice that if Γ 1 and Γ 2 are isoaxial Fuchsian groups, then for any γ ∈ Γ 2 ax(Γ 1 ) = ax(γΓ 1 γ −1 ), and therefore γ ∈ Aut(ax(Γ)).…”
Section: Arithemetic Groupsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the case of Fuchsian groups of the first kind Long and Reid [4] proved the conjecture for arithemetic groups. Also notice that if Γ 1 and Γ 2 are isoaxial Fuchsian groups, then for any γ ∈ Γ 2 ax(Γ 1 ) = ax(γΓ 1 γ −1 ), and therefore γ ∈ Aut(ax(Γ)).…”
Section: Arithemetic Groupsmentioning
confidence: 97%
“…In the case of Fuchsian groups of the first kind Long and Reid [4] proved the conjecture for arithemetic groups.…”
Section: Arithemetic Groupsmentioning
confidence: 97%
“…Recall that two Fuchsian groups are defined to be isoaxial if they share the same set of axes in H 2 . If both the Fuchsian groups are assumed arithmetic, then [12] shows they are commensurable (without conjugating). There is considerable experimental evidence that the pseudomodular groups we know of are not isoaxial with SLð2; ZÞ; for example it would appear that if A denotes the axis of the element but M k is in Dð5=7; 6Þ, then k e 36 and 4jk.…”
Section: Does Dðumentioning
confidence: 99%
“…In 1990, G. Mess [11] showed that if G 1 and G 2 are non-elementary finitely generated Fuchsian groups having the same nonempty set of simple axes, then G 1 and G 2 are commensurable. Using some technical results on arithmetic Kleinian groups, D. Long and A. Reid [9] gave an affirmative answer to this question in the case where G 1 and G 2 are arithmetic Kleinian groups. Note that all the confirmed cases for the question are geometrically finite groups.…”
Section: Introductionmentioning
confidence: 99%